BREEDING EFFICIENCY OF BEEF CATTLE IN CHINESE SUITABLE AREAS - Yong Jie Xue; Jin Ling Yan (Journal of Animal and Plant Sciences, 2019)
Beef has been considered a semi-luxury by Chinese residents, as its price is significantly higher than other meats, like pork and chicken. Rising disposable income of residents has contributed to the growth of beef consumption in China. And the potential of beef market is enormous. Based on the panel data from 2007 to 2016, this paper uses SBM (Slacks Based Measure of Efficiency) to calculate the productive efficiency of beef cattle breeding in china, analyze each breeding area’s spatial and temporal distribution characteristics, and explore the factors influencing the efficiency. The results prove that: (1)The beef cattle breeding efficiency in China was much lower than expected，there are input-output slacks in nearly all areas in different degree. (2) the net efficiency of beef cattle breeding did not show a significant upward trend, while the growth range was quite different among regions. The agricultural areas in central plains have higher efficiency and obvious annual upward trend than the northwest and northeast pastoral areas in China. (3) Beef cattle breeding model and geographical location conditions are important factors affecting the net breeding efficiency.
Keywords: China; Beef cattle breeding; SBM model; productive efficiency